Switching Opioid‐Dependent Patients From Methadone to Morphine: Safety, Tolerability, and Methadone Pharmacokinetics. (29th February 2016) - Glue, Paul; Cape, Gavin; Tunnicliff, Donna; Lockhart, Michelle; Lam, Fred; Gray, Andrew; Hung, Noelyn; Hung, C. Tak; Harland, Sarah; Devane, Jane; Howes, John; Weis, Holger; et al.
Abstract: The aim of this study was to switch patients established on methadone opioid substitution therapy (OST) to morphine over 1 week. Subjects established on daily methadone OST (mean dose 60 mg/day) were switched to morphine slow‐release capsules, dosed at 4× the previous total daily methadone dose, for 6 days, then given morphine syrup dosed q3h. All 27 subjects enrolled in this study completed the switch from methadone to morphine. Opioid withdrawal symptoms (OWS) peaked within 12–24 hours of starting morphine, and 24/27 subjects required higher daily morphine doses (mean 5.2× multiple). Pharmacokinetic evaluation showed that 91% of methadone was cleared during this time, with a mean elimination half‐life of 59 hours. The most frequent treatment‐emergent non‐OWS adverse events were headache, nausea, constipation, and neck pain. The method described here appears to be a safe and acceptable approach to switch subjects from methadone to morphine.